NILAI PENDIDIKAN KARAKTER DALAM CERITA RAKYAT SASAK ”DOYAN NADA” - Alpan Ahmadi (JURNAL ILMIAH GLOBAL EDUCATION, 2021)
This study aims to describe the character values ​​contained in the Sasak folklore "Doyan Nada". The research data of this research is folklore obtained from reading a book entitled "Folks from Lombok (West Nusa Tenggara) by G. Parman and Slamet Riyadi Ali. The method used in this research is descriptive qualitative. The data collection technique used is reading and note-taking technique. The results showed that the values ​​of character education contained in the Doyan Nada folklore were very good for the formation of the character of the reader. The value of character education contained in the Doyan Nada folklore covers the values ​​contained in society, so that it will be able to contribute to social life. The values ​​of character education contained in the Doyan Nada folklore, namely the attitude of caring for others, the value of courage, and the value of compassion for others